Sub-nanosecond acousto-electric carrier redistribution dynamics and transport in polytypic GaAs nanowires. (18th October 2021) - Sonner, Maximilian M; Gnedel, Maximilian; Berlin, Johannes C; Rudolph, Daniel; Koblmüller, Gregor; Krenner, Hubert J
Abstract: The authors report on a combined structural, optical and acousto-electric study of polytypic GaAs nanowires. Two types of nanowires with different zincblende and wurtzite crystal phase mixing are identified by transmission electron microscopy and photoluminescence spectroscopy. The nanowires exhibit characteristic recombination channels which are assigned to different types of spatially direct recombination (electron and hole within the same crystal phase segment) and spatially indirect recombination (electron and holes localized in different segments). Contact-free acousto-optoelectric spectroscopy is employed to resolve spatiotemporal charge carrier dynamics between different recombination channels induced by a piezoelectric surface acoustic wave. The observed suppression of the emission and its dynamic temporal modulation shows unambiguous fingerprints of the local bandedge variations induced by the crystal phase mixing. A nanowire, which exhibits a variation from a near-pristine zinc blende crystal structure to a highly mixed crystal phase, shows a clear dependence on the propagation direction of the acoustic wave. In contrast, no pronounced directionality is found for a nanowire with an extended near-pristine zincblende segment. The experimental findings are corroborated by solving the drift and diffusion equations of electrons and holes induced by the surface acoustic wave. The key characteristics observed in our experimental data are well reproduced in the numerical simulations by assuming two general bandedge modulations and realistic parameters for the bandedge discontinuities and transport mobilities of electrons and holes. This evidences that even all relevant physical processes are accounted for in the model.